Sosialisasi dan Pendampingan Budidaya Kelapa Genjah sebagai Upaya Mitigasi Risiko Kecelakaan Penderes dan Optimalisasi Produksi Nira - Dian Novitasari; Henggar Jaya, Gigieh; Miftahol Arifin; Nabila Noor Qisthani; Aswan Munang (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2025)
Indonesia is a tropical country with the largest coconut production in the world, but the productivity and safety of tappers are still challenges, especially in Pernasidi Village, Banyumas. The main problem is the high dominance of coconuts and the risk of accidents for elderly tappers. As a solution, community service was carried out through socialization and assistance in cultivating shorter and more productive dwarf coconuts. The activity was carried out by a team of lecturers from Unsoed and Telkom University from October to December 2024, involving local farmer groups. The methods used included counseling, field practice, and assistance. The socialization material included the characteristics of dwarf coconuts, cultivation techniques, and their advantages. A total of 250 Entog Genjah seedlings were used in the planting practice. The results showed a significant increase in participant knowledge based on the pretest and posttest. Direct practice strengthens farmers' technical skills, while ongoing assistance ensures the implementation of knowledge in the field. Evaluation through FGD showed the enthusiasm of participants, as evidenced by the formation of new farmer groups and partnership proposals to the local government. In conclusion, this program has succeeded in increasing the capacity of farmers in dwarf coconut cultivation and encouraging collective initiatives. It is recommended that institutional development of farmers and ongoing support from the government be carried out, especially in the provision of superior seeds and advanced training to strengthen the adoption of technology and the sustainability of coconut sap production.